Management of pregnant women with Refractory Immune Thrombocytopenia Purpura (ITP) receiving eltrombopag therapy at Sanjiwani Hospital, Gianyar, Indonesia - Anak Agung Raka Budayasa; Cokorda Gede Angga Ary Nugraha (DiscoverSys Inc., 2021)
Background: Immune Thrombocytopenia Purpura (ITP) is an autoimmune disease characterized by a low level of platelets in the blood caused by accelerated platelet destruction or disruption of the thrombopoiesis due to antibodies to platelets. Drugs with similar functions to thrombopoietins (TPO) such as eltrombopag and romiplostim have been widely used and have been shown to be quite successful in treating ITP in nonpregnant patients. This case study aims to evaluate eltrombopag therapy's role in managing the refractory ITP in pregnant women.Case Presentation: A 25-year-old patient, a housewife, presented to the obstetrics clinic at Sanjiwani Hospital for the first time at a gestational age of 13 weeks for her third pregnancy, with a history of two abortions. ITP was diagnosed in 2017 during the second abortion treatment. The platelet examination results were between 32,000-66,000/?l, with platelet count during delivery planning at 34 weeks of 41,000/?l. The patient was diagnosed with chronic refractory ITP and was considered for second-line drug administration. Intravenous Immunoglobulin Therapy (IVIG) and anti-D administration as second-line drugs were not possible due to cost. The patient was given 50 mg eltrombopag per day for a week. The platelet counts increased to 202,000/?l a week after therapy. The patient then underwent vaginal delivery with a baby weight of 2,850 gram, Apgar Score of 8-10. The baby was exclusively breastfed and subjected to clinical monitoring and laboratory tests. The patient's clinical condition was favorable and the platelets fell to 20,000/?l nineteen days after delivery.Conclusion: In this case, the patient with chronic ITP refractory to steroid therapy showed an immediate response to eltrombopag. However, the platelet level decreased two weeks after the treatment cessation. More studies are needed on the use of eltrombopag in pregnant women.